Plyometric Training on Grass Surfaces on Women's Vertical Jump in Volleyball - Ai Mulyatini; Dede Rohmat Nurjaya; Yopi Kusdinar (Universitas Negeri Semarang, 2025)
This study aim for know impact exercise plyometric on the surface grass to volleyball vertical jump daughter. Research This use method quantitative with design One-Group Pretest-Posttest Design. Sample consists of of 20 athletes Allexis club princess aged 14-16 years, with using total sampling. Subject done with One group experiment accept exercise plyometric on the surface grass. The instrument used For measure vertical jump is slapstick test/ Vertec . Data analysis in study This using SPSS 26 test. Hypothesis test results show that there is difference significant (p<0.05) between pre-test and post-test scores, which indicate that hypothesis study accepted. In descriptive, average score vertical jump increase from 32.15 cm in the pre-test to 35.35 cm in the post-test after undergo 12 sessions exercise plyometric during One month. This average increase show existence change positive that describes the influence of the training program provided. Therefore that, can concluded that there is significant impact exercise plyometric on the surface grass to volleyball vertical jump daughter.